Ultralong CH3NH3PbI3 nanowires synthesized by a ligand-assisted reprecipitation strategy for high-performance photodetectors. Issue 22 (5th May 2020) - He, Xu; Jian, Chuanyong; Hong, Wenting; Cai, Qian; Liu, Wei
Abstract : Organic–inorganic hybrid perovskite nanowires with well-defined structures have attracted considerable attention for optoelectronic applications. Abstract : Organic–inorganic hybrid perovskite nanowires with well-defined structures have attracted considerable attention for optoelectronic applications. Perovskite nanowires integrated into practical optoelectronic devices are often hindered by the poor crystalline quality. Herein, a ligand-assisted reprecipitation (LARP) strategy is employed to prepare ultralong and freestanding CH3 NH3 PbI3 nanowires on a large-scale. Oleylamine is adopted as an inhibitor, which can create a passivation layer on the surface of CH3 NH3 PbI3, to slow down the crystallization rate of CH3 NH3 PbI3 nanowires. With the low crystallization rate, several millimeters long and high-quality CH3 NH3 PbI3 nanowires with smooth surfaces can be synthesized on a large scale. Photodetectors fabricated on oleylamine assisted synthesized CH3 NH3 PbI3 nanowires exhibit high detectivity, which is five times higher than that of non-oleylamine assisted synthesized CH3 NH3 PbI3 nanowire photoanodes.